A formação dos juízos éticos nos ciberespaços das relações humanas sob o viés da compreensão política de Hannah Arendt - Candido, Cristiane Roberta Xavier (2021)
This research has as its purpose the analysis of the possibility of training ethical judgements among human beings when they find themselves inserted in the virtualized context of the world, such as the cyberspaces of internet social networks. Therefore, the identification of this research’s problem is given based on the political thinking of the philosopher Hannah Arendt (1906-1975) who seeks to highlight the realization of human relations in an authentic (and not alienated) way through the maintenance of the common sense of world and the action provided in a public sphere based on plurality. The problem considered by this research is found in the middle ground existing between what we know today as the world of human relations in the virtual sphere of the internet and the world as Arendt identifies, so that the question which stands out is: Is it possible to establish a common sense of world within cyberspaces and, by correspondence, to make (impartial and responsible) ethical judgments about others in this between-space of the virtual environment relationships? Thus, to analyze these points, the specific goals of this research unfold in order to: present the case of Nazism in Germany (as the most original example of totalitarianism) in order to clarify an experience in which plurality and action are suppressed and, therefore, the public sphere is non-existent; to identify the way in which the author develops her ideas about the concept of vita activa, as well as the importance level of the concepts of action and plurality as a criteria for the maintenance of the public sphere and, accordingly, in the understanding of human relations steered towards respect and freedom; highlight the concept of world effectivated in Arendtian analyzes which, starting from the idea of common sense, offers the basis for the authentic existence of men; and, emphasize the need for understanding as a factor that provides subsidies and enables the faculty to judge, in addition to impartially organizing the intelligible capacity (of thought) in a way uncoupled from the exclusivity of private analyses, thus aiming at the articulation between the public and private so that the latter does not become the exclusive thread of judgments. Hence, this research presents itself as relevant since it seeks to articulate the need for questioning the virtual world of human social networks in order to identify whether it offers a condition for maintaining plurality as a sine qua non criteria of the public sphere and, consequently, of the authentic existence of the world. Based on what is expected in relation to the results, the goal is for it to be possible to understand what the virtual world is and if there is in fact a common sense of this world so that, through the communication networks of this cyberspace , men are able to reveal themselves and maintain plurality and, therefore, carry out (impartial and responsible) ethical judgments.